2021
DOI: 10.1148/radiol.2021201852
|View full text |Cite|
|
Sign up to set email alerts
|

Tomoelastography Based on Multifrequency MR Elastography for Prostate Cancer Detection: Comparison with Multiparametric MRI

Abstract: T he incidence of prostate cancer (PCa) has increased by 42% worldwide since 2007 (1). Early and accurate diagnosis is of great importance for prognosis and for planning treatment. In clinical routine, the likelihood of clinically significant PCa is assessed by using the Prostate Imaging Reporting and Data System (PI-RADS), which incorporates anatomic and functional information acquired by using multiparametric MRI (2,3). This diagnostic MRI pathway with subsequent biopsy-based histopathologic confirmation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Although this frequency range is too limited for analysis of viscoelastic dispersion in zebrafish tissue, previous work has shown that even minimal variation of excitation frequency enhances the stability of the inverse problems solution for the reconstruction of MRE maps using our k-MDEV (multifrequency dual elasto-visco) algorithm. 36,37 For testing spatial resolution and SNR using the ultrasound gel phantom, matrix sizes of 100 × 100, 67 × 67, 50 × 50, and 40 × 40 were used with a 4 × 4 mm 2 FOV, resulting in in-plane pixel sizes of 40 × 40 µm 2 , 60 × 60 µm 2 , 80 × 80 µm 2 , and 100 × 100 µm 2 , respectively. Based on the results of the phantom experiment, we used the following parameters to measure the fish: 8 axial slices of 600 µm thickness, 67 × 67 matrix size, 4 × 4 mm 2 FOV, and an in-plane resolution of 60 × 60 µm 2 .…”
Section: Mre Image Acquisitionmentioning
confidence: 99%
“…Although this frequency range is too limited for analysis of viscoelastic dispersion in zebrafish tissue, previous work has shown that even minimal variation of excitation frequency enhances the stability of the inverse problems solution for the reconstruction of MRE maps using our k-MDEV (multifrequency dual elasto-visco) algorithm. 36,37 For testing spatial resolution and SNR using the ultrasound gel phantom, matrix sizes of 100 × 100, 67 × 67, 50 × 50, and 40 × 40 were used with a 4 × 4 mm 2 FOV, resulting in in-plane pixel sizes of 40 × 40 µm 2 , 60 × 60 µm 2 , 80 × 80 µm 2 , and 100 × 100 µm 2 , respectively. Based on the results of the phantom experiment, we used the following parameters to measure the fish: 8 axial slices of 600 µm thickness, 67 × 67 matrix size, 4 × 4 mm 2 FOV, and an in-plane resolution of 60 × 60 µm 2 .…”
Section: Mre Image Acquisitionmentioning
confidence: 99%
“…Although MRE of the prostate is not yet part of standard care imaging, the proposed segmentation tool may help to further integrate this innovative imaging marker into routine clinical practice. We are confident that MRE will add diagnostic value to the PIRADS system in the future as shown in 53 . In addition, when enhanced with the segmentation option presented here, MRE may provide quantitative values on the mechanical consistency of prostate subzones as a reference for fully automated tumor classification.…”
Section: Discussionmentioning
confidence: 88%
“…With multifrequency data acquisition and wavenumber-based inversion method, the parameter maps provided by tomoelastography can reveal rich anatomical details [ 34 ]. Tomoelastography provides two viscoelastic parameters for biomechanical characterization of soft tissues [ 35 ]: shear wave speed ( c , m/s) and loss angle of the complex shear modulus ( φ , rad), which are surrogate indicators of stiffness and viscosity (or fluidity), respectively, through postprocessing. Tomoelastography has been applied for the biomechanical characterization of a variety of diseases in vivo, including pancreatic diseases [ 30 , 36 ], neuro-tumors [ 37 ], prostate diseases [ 35 , 38 ], rectal carcinoma [ 32 ], inflammatory bowel disease[ 39 ], liver tumors [ 29 , 40 ], and chronic liver disease [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tomoelastography provides two viscoelastic parameters for biomechanical characterization of soft tissues [ 35 ]: shear wave speed ( c , m/s) and loss angle of the complex shear modulus ( φ , rad), which are surrogate indicators of stiffness and viscosity (or fluidity), respectively, through postprocessing. Tomoelastography has been applied for the biomechanical characterization of a variety of diseases in vivo, including pancreatic diseases [ 30 , 36 ], neuro-tumors [ 37 ], prostate diseases [ 35 , 38 ], rectal carcinoma [ 32 ], inflammatory bowel disease[ 39 ], liver tumors [ 29 , 40 ], and chronic liver disease [ 41 , 42 ]. Because microstructural properties in the ECM and cell conditions alter liver fibrosis progression, we hypothesized that stiffness and fluidity, mostly associated with the ECM constituents, could indicate hepatic pathological processes and may reflect liver function [ 43 ].…”
Section: Introductionmentioning
confidence: 99%